BS IEC 62282-4-600. Fuel cell technologies. Part 4-600. Fuel cell power systems for propulsion other than road vehicles and auxiliary power units (APU). Fuel cell and battery hybrid power pack systems performance test methods for excavators (29th May 2020) - British Standards Institution
No abstract available